SISTEM INFORMASI PENGOLAHAN DATA KRIMINAL PADA KANTOR DENPOM II/2 JAMBI BEBRBASIS VB NET : Information System, Criminal Data, Visual Basic., XAMPP, Mysql. - Elzas, Elzas; Afrizal, Afrizal; Yunita, Yunita (JURNAL AKADEMIKA, 2025)
This study aims to build a Criminal Data Processing Information System at the Office of Denpom II/2 Jambi based on VB Net, the research method is basically a scientific way to obtain data with certain purposes and uses. The research objectives can be determined based on the identification and analysis of problems from the previous step with the new system, namely the criminal data processing information system at the Jambi Denpom II/2 Office, the speed in making the required reports can be increased and the delays that have occurred due to the accumulation of data and the large number of data that will be processed in a short time can be handled quickly and precisely. By using a computer-based criminal data information system program using the Visual Basic programming language, it can automatically increase efficiency and reduce human errors. The design using computers and programs for making reports in the desired information will be faster because the data has been stored in files in storage media so that there is no repetitive work and if at any time the information is needed it can be tracked back or can be done right away.